Design of Clean Water Distribution System in Saibi Samukop Village - Medyawanti Pane; Amos Amos; Rahmad Samosir (VANOS Journal of Mechanical Engineering Education, 2022)
In Saibi Samukop Village some wells are used by the community for daily needs, but the water is drawn from the wells using a bucket simultaneously, so the water becomes cloudy. For this reason, researchers designed a clean water distribution system using 2 100 Wp solar panels to charge 2 batteries to turn on the pump. The pump specifications used have a maximum power of 180 Watts, a Head of 15 meters with 12 Volts. From the test results with a head of 9.32 meters, the required power is 67 Watts and a strong current of 5.5 Ampere so that it can run the pump for 17 hours. Based on the need for clean water in Saibi Samukop Village for Massogunei Hamlet of 1053 liters/day and Pangasaat Village of 9420 liters/day, the pump is required to operate for 6.03 and 6.4 hours/day with pump efficiency of 34%.